THE CORRELATION OF PREECLAMPSIA IN PREGNANCY WITH THE INCIDENCE OF ASPHYXIA NEONATORUM AT THE MANGUSADA BADUNG REGIONAL HOSPITAL IN BALI FROM JANUARY 2017 – DECEMBER 2020 - Ni Putu Cintya Giri Putri; Edwin Budipramana; Dini Andriani (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Introduction: Preeclampsia is included as one of hypertension in pregnancy, with the prevalence still quite high now. This condition increases maternal and perinatal mortality and morbidity. Preeclampsia causes decreased oxygen supply from mother to fetus due to systemic vasoconstriction. So, it can cause the fetus to be born in a state of asphyxia (neonatal asphyxia).Purpose: To determine the correlation between preeclampsia in pregnancy and the incidence of asphyxia neonatorum at the Mangusada Badung Regional Hospital in Bali from January 2017 – December 2020.Method: The research used an analytic observational study with a case-control design. The sampling technique used in this research is probability sampling with simple random sampling. Sample selected from members of the population based on the inclusion and exclusion criteria that have been set. The total sample used was 268 newborns, divided into 2, the case group and the control group. The statistical test used is Spearman's rho.Result: From 134 sample cases, 65 samples were from mothers with preeclampsia diagnosed, and 69 samples were from mothers without preeclampsia diagnosed. Of the 134 control samples, 31 samples were from mothers with preeclampsia diagnosed, and 103 samples were from mothers without preeclampsia diagnosed. The results of the test using Spearman's rho p = 0.000 and the results of the analysis Odds Ratio OR = 3.13.Conclusion: There is a significant correlation between preeclampsia with the incidence of neonatal asphyxia at the Mangusada Badung Regional Hospital from 1 January 2017 – 31 December 2020.